Effect of diabetes mellitus as a modifier with periodontitis severity and oral health–related quality of life in older adults: a cross-sectional study - Utami, Sri; Kusnanto, Hari; Pramono, Dibyo; Ratna Astuti, Novitasari Ratna; Hasnasari Heningtyas, Afina; Oktavia, Nova; Afrilyana Ulzanah, Fannisa (Universitas Padjadjaran, 2026)
Introduction: The main complication of diabetes mellitus (DM) in the oral cavity is periodontitis. Periodontitis is one of the conditions that affects quality of life because it causes psychological discomfort, stress, interpersonal relationship problems, and difficulties in daily activities. The objective of this study was to analyze the effect of diabetes mellitus as a modifier with periodontitis severity and oral health–related quality of life in older adults. Methods: This study is a cross-sectional study, where this design can be used to provide the groundwork to infer preliminary evidence for a causal relationship. The subjects were 302 elderly individuals aged ≥ 60 years who still had at least 6 teeth representing 6 regions. The study variables were the severity of periodontitis, Oral Health-Related Quality of Life (OHRQoL), and diabetes mellitus (DM). Periodontitis was diagnosed using the classification from the American Association of Periodontology (AAP) and the European Federation of Periodontology (EFP) in 2018, using the Clinical Attachment Loss (CAL) indicator. The Geriatric Oral Health Assessment Index (GOHAI) was used to measure OHRQoL. DM status was diagnosed using HbA1c levels. Data analysis was performed using multiple linear regression with a significance level of 0.05. Results: The majority of participants had severe periodontitis (73.8%) followed by moderate periodontitis (22.2%) and mild periodontitis (4%). The results of multiple linear regression analysis showed that there was an interaction between uncontrolled DM and periodontitis on OHRQoL (Adj.β = -11, p=0.05). Conclusions: Diabetes mellitus acts as a modifier effect on the relationship between the severity of periodontitis and OHRQoL. The more severe the periodontitis, the lower the OHRQoL. Uncontrolled DM influences the direct relationship between periodontitis severity and OHRQoL. The relationship between periodontitis severity and OHRQoL is stronger and more pronounced in uncontrolled DM